PERSEPSI WARGA BELAJAR TERHADAP TIPE KEPEMIMPINAN KETUA YAYASAN DI PKBM PELITA RIAU KOTA PEKANBARU - Celeste S, Yolanda De; Sumardi, Sumardi; Achmad, Said Suhil (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was motivated by the background to find out the perceptions of people who learned about the leadership of the chairman of the foundation in PKBM Pelita riau Pekanbaru city. The formulation of the problem from this research is whether the perceptions of citizens learn about the leadership of the chairman of the foundation in Pelita Riau PKBM Pekanbaru City? The purpose of this study was to determine the perceptions of the learning community towards the leadership of the chairman of the foundation in Pelita Riau PKBM Pekanbaru City. The population in this study were 60 people who studied. Then the sample of this study was 38 study residents and 20 residents studying experimental samples with a critical level of 10%, samples which were simple random samples. The instrument for sending data is a questionnaire with 72 statements and applies to experiments that apply to research instruments. Based on the results of the news, the average of 5 indicators of the average value for the perception variable of the learning citizens towards the chairman of the foundation in Pelita Riau, PKBM, Pekanbaru City is relatively good, that is, with Mean 3.67 and SD 0.82. The interpretations obtained for each learning indicator of citizens learn about the foundation in Pelita Riau PKBM Pekanbaru City are all good. So the learning community considers the chairman of the foundation to use a free but democratic educational institution.Keywords: Perception of learning citizens, leadership of the chairman of the foundation